Edukasi Pola Hidup Bersih dan Sehat Remaja di Desa Pemecutan Kelod - Nazlah, Alifatul; Wardani, Kadek Devi Kalfika Anggria (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The emergency caused by the Covid-19 pandemic has brought many changes in human life. Pemecutan Kelod Village as one of the villages with a fairly high rate of Covid-19 spread in Denpasar requires immediate action to flatten the curve of confirmed Covid-19 cases. Community service activities, through education to teenagers related to the Implementation of a Clean and Healthy Lifestyle (PHBS) for teenagers were chosen as one of the strategic steps. With the education provided, it is hoped that they can 1) make teenagers aware of the importance of PHBS; 2) assisting teenagers to become agents of reform to help suppress the spread of Covid-19. By utilizing the e-learning method assisted by media zoom, education is carried out for teenagers. The presentation of educational materials focused on two main materials. The first material is related to PHBS and its application in daily life. The second material given is about basic actions that teenagers can take when they suspect people in their surrounding environment have Covid-19 symptoms. The final result of this service activity; 1) Pemecutan Kelod Village youth have knowledge about PHBS and its important role in preventing the expansion of Covid-19. 2) Pemecutan Kelod Village youths have knowledge of basic actions when finding a suspected case of Covid-19.